Assessment of the quality of groundwater sources in Sitio Gines-Tacas, Brgy. Palaca, Miag-ao, Iloilo - Divinagracia, Sheila Marie Suanque (2002.)
The quality of selected groundwater sources in Sitio Gines-Tacas Brgy. Palaca, Miag-ao, Iloilo was assessed.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Groundwater sources; Water-supply.